Morphology and reproduction of the common opossum (Didelphis marsupialis) dwelling in urban vs rural environments in Antioquia, Colombia - Ceballos, Claudia P; Hernández Montoya, Viviana; Caicedo, Juliana; Castillo Vanegas, Viviana E (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Although urban wildlife has increased during the last years, the effects of urbanization on wildlife are poorly understood. Common opossum (Didelphis marsupialis) is a frequent dweller of the Metropolitan Area of Valle del Aburrá (AMVA) in the Antioquia province (Colombia) where opossum-human conflicts result in large numbers of injured or dead opossums. Objective: To evaluate the effects of urban and rural habitats on the morphometry and reproductive output (litter size in marsupium) of opossums. Methods: A total of 131 opossums were captured: 94 in the AMVA, and 37 in rural areas of Antioquia. Opossums were weighed, measured, sexed, clinically inspected, and photographed. Results: Urban opossums were heavier and larger than rural individuals, regardless of sex, and no differences were observed in terms of reproductive output between both habitats. Additionally, urban opossums were more abundant than rural opossums, possibly explained by the fact that cities favor survival -through higher food availability- but not reproduction. Alternatively, bigger animals could also be explained by inadequate diets rich in carbohydrates which may also have deleterious health effects. We observed sexual size dimorphism in head and tail length but not in body length of opossums. Conclusion: We confirm that urban environments have a significant effect on body mass and size of opossums; however, it is unknown whether this is beneficial or detrimental for these animals. Finally, we report the lowest litter size for the species, with no difference between rural and urban habitats.